Literature Study on the Importance of Differentiated Strategy Approach to Biology Learning in Senior High School - Putri, Apriliana Dwi; Susanti, Rahmi (Magister Pendidikan Biologi, Universitas Negeri Medan, 2023)
Knowledge of understanding differentiating strategies is still not widely known by educators so that in journals the study of literature aims to describe the differentiating approach strategies in schools as reading material for knowledge to adapt learning based on the needs of students regarding aspects of content, processes, products, and a comfortable learning environment. This research method uses a literature study approach by collecting references consisting of several previous studies which are then combined to draw conclusions from the readings included in qualitative research, namely research that uses a natural setting with the intention of interpreting the phenomena that occur and is carried out by involving various methods which exists. The results of the study show that students feel comfortable when educators apply the process of learning activities according to the needs of students so that the implementation is in accordance with the theory for reference to applying learning and knowing the opinions of students regarding differentiated learning strategies. The conclusions in the literature review serve as reference material for implementing a differentiated learning process in the classroom so that there is behavior to adjust learning with learning readiness to achieve learning goals and can be used for further research material related to the implementation of the application of a differentiated approach and is useful for designing steps using learning strategies differentiate according to the needs of students in the school environment and implementation in society and advanced research materials for implementation in the school environment.